2022
DOI: 10.1140/epjc/s10052-022-11123-0
|View full text |Cite
|
Sign up to set email alerts
|

Gliner vacuum, self-consistent theory of Ruppeiner geometry for regular black holes

Abstract: In the view of the Gliner vacuum, we remove the deformations in the first law of mechanics for regular black holes, where one part of deformations associated with black hole mass will be absorbed into enthalpy or internal energy, and the other part associated with parameters rather than mass will constitute a natural V–P term. The improved first law of mechanics redisplays its resemblance to the first law of thermodynamic systems, which implies a restored correspondence of the mechanic variables to the thermod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Ref. [20] suggested that dM in the first law needs a coefficient that is not always equal to 1, which is followed up by many authors [10,[20][21][22][23] and leads to a very different form of the first law and Smarr formula. Such modifications suffer the problems of parameter non-independence [11,[24][25][26] and non-extensiveness.…”
Section: Jcap03(2024)053mentioning
confidence: 99%
“…Ref. [20] suggested that dM in the first law needs a coefficient that is not always equal to 1, which is followed up by many authors [10,[20][21][22][23] and leads to a very different form of the first law and Smarr formula. Such modifications suffer the problems of parameter non-independence [11,[24][25][26] and non-extensiveness.…”
Section: Jcap03(2024)053mentioning
confidence: 99%
“…Moreover, these parameters must appear in σ via the combinations , which are also dimensionless. If every combination includes a non-zero , we can reduce one parameter and obtain independent dimensionless parameters by following the Buckingham π theorem [32].…”
Section: Realistic Regular Black Holesmentioning
confidence: 99%
“…However, the objective of the present manuscript is to study black holes. It is worth mentioning that in reference [70], the radial pressure of the Gliner vacuum at the event horizon (given by p r | r=r h = −ρ| r=r h , where the energy density corresponds to the pure Dymnikova case, equation (2.2), is related with the thermodynamics pressure of the black hole, which leads to a version of the first law of thermodynamics for RBHs. Following this approach, but relating the GUP corrected energy density (2.7) with the thermodynamic pressure, the structure of the first law of thermodynamics using α as a thermodynamics variable will be explored in a separate publication.…”
Section: Jcap11(2023)100mentioning
confidence: 99%